2010
DOI: 10.1074/jbc.m110.180505
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Aromatic Residue in the Autochaperone Domain of the Autotransporter Hbp Is Critical for Initiation of Outer Membrane Translocation

Abstract: Autotransporters are bacterial virulence factors that share a common mechanism by which they are transported to the cell surface. They consist of an N-terminal passenger domain and a C-terminal ␤-barrel, which has been implicated in translocation of the passenger across the outer membrane (OM). The mechanism of passenger translocation and folding is still unclear but involves a conserved region at the C terminus of the passenger domain, the so-called autochaperone domain. This domain functions in the stepwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 48 publications
2
80
0
Order By: Relevance
“…We then investigated the ability of the meningococcal TpsBs to secrete TPS domains of N. lactamica, since this is a closely related bacterial species that occupies the same niche in the human body. Like in N. meningitidis, several TPS systems have been identified in N. lactamica, and not all appear to have a dedicated TpsB encoded (35,36). Furthermore, sequence comparisons of TPS domains showed that the systems in N. meningitidis and N. lactamica are related (see Table S2 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…We then investigated the ability of the meningococcal TpsBs to secrete TPS domains of N. lactamica, since this is a closely related bacterial species that occupies the same niche in the human body. Like in N. meningitidis, several TPS systems have been identified in N. lactamica, and not all appear to have a dedicated TpsB encoded (35,36). Furthermore, sequence comparisons of TPS domains showed that the systems in N. meningitidis and N. lactamica are related (see Table S2 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…Position 453 lies within the first predicted ␤-strand of the N-terminal extracellular domain (D00) of the passenger Thus, the introduced double HA tag presumably leads to misfolding of the D00 domain. Tsai et al (13) assumed that this domain could function as an autochaperone domain as it was described for classical monomeric autotransporters (31)(32)(33). Such domains initiate the vectorial export of the passenger by forming a hairpin intermediate and improve transport efficiency.…”
Section: Intha453 Is Expressed At the Wild Type Level And The ␤-Barrementioning
confidence: 99%
“…sory factors assisting in translocation of passenger domains across the OM (5,22) and stabilizes these otherwise transient protein-protein interactions in whole cells. After cross-linking, E. coli cells expressing Pet48aa, Pet1HA, and Pet1HA-FLAG were harvested, spheroplasted, and lysed, and membrane proteins were co-purified with immobilized anti-Pet passenger domain antibody.…”
Section: Native Cys Residues Are Not Required For Secretion or Foldinmentioning
confidence: 99%